1981
DOI: 10.1007/bf00439062
|View full text |Cite
|
Sign up to set email alerts
|

Toxigenicity of fungi from grain sorghum

Abstract: The mycoflora of nine varieties of grain sorghum was determined by plating serial dilutions of ground samples on rose bengal-streptomycin agar. Seventeen species of fungi representing 10 genera were identified. Curvularia, Penicillium, Mucor, and Aspergillus were dominant genera. Extracts of P. herquei were highly toxic to brine shrimp, while those of C. clavata, C. lunata, and Mucor mucedo showed low to moderate toxicity. Extracts of C. clavata, C. lunata, and M. mucedo were highly toxic to chicken embryos; t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
2

Year Published

1984
1984
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 15 publications
1
8
2
Order By: Relevance
“…This may be probably attributed mainly to the bad storage condition. These results were coincided with those reported by many investigators Diener et al, 2 Gonzaleze et al, 3 Bhat et al Toxin production by some toxigenic fungi isolated from sorghum grains collected from different governorates…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…This may be probably attributed mainly to the bad storage condition. These results were coincided with those reported by many investigators Diener et al, 2 Gonzaleze et al, 3 Bhat et al Toxin production by some toxigenic fungi isolated from sorghum grains collected from different governorates…”
Section: Resultssupporting
confidence: 92%
“…Penicillium and Aspergillius were Alternaria, Penicillium sorghuma, Penicillium funiculosum and Aspergillus flavus, respectively. Diener et al, 2 Gonzalez et al 3 Outbreaks of aflatoxicosis in farm animals have been reported from many areas of the world. The liver is mainly affected in such outbreaks and also in experimental studies on animals, including nonhuman primates.…”
Section: Introductionmentioning
confidence: 99%
“…Fungi causing deterioration have always been a major concern in cereals, such as sorghum, maize and paddy, because of their ability to produce mycotoxins. Fungi, especially those belonging to the genera Aspergillus and Fusarium , have been reported to occur at high incidence on cereal grains (Diener et al. 1981; Abdel‐Hafez et al.…”
Section: Discussionmentioning
confidence: 99%
“…Millions of people in the semi‐arid tropics of Asia and Africa depend on this crop for their staple diet. The quality of sorghum grains, particularly after wet weather in the early or late monsoon is often lowered, following colonization by fungi and with the subsequent accumulation of mycotoxins (Diener et al. 1981; Wilson et al.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of deteriorative fungi with ability to produce mycotoxin in grains and food represents a great hazard for human and animal health, and it has been reported for sorghum in many countries with a high frequency of Aspergillus and Fusarium genera (1,7,11,10,25).…”
Section: Introductionmentioning
confidence: 99%